Routiers’ transformational trajectories of waste, from Portugal to Senegal - Neto, P.; Falcão, R. (Border crossings in and out of Europe, 2022)
Routiers are men of African origin that regularly drive decades-old vehicles from Southern Europe to West Africa. In their vehicles they carry a set of second-hand items which are sold, traded, and/or bartered along the way. This essay offers a collection of images that depict and interrogate some of the symbolic, socioeconomic, and spatiotemporal qualities of routier activity while fostering an understanding of the transformational trajectories of the items handled – from discarded, disposable, virtually valueless things into things of/with value, sometimes, reconverted, reemployed, replaced, resettled.